Associations between birth at, or after, 41 weeks gestation and perinatal encephalopathy: a cohort study. Issue 1 (24th January 2018) - Odd, David E; Yau, Christopher; Winter, Cathy; Draycott, Timothy; Rasmussen, Finn
Abstract : Background: Preterm birth causes long-term problems, even for infants born 1 or 2 weeks early. However, less is known about infants born after their due date and over a quarter of infants are born over 1 week late, and many still remain undelivered after 2 weeks. The aim of this work is to quantify the risks of infants developing encephalopathy when birth occurs after the due date, and if other proposed risk factors modify this relationship. Methods: The dataset contain information on 4 036 346 infants born in Sweden between 1973 and 2012. Exposure was defined as birth 7, or more, days after the infants' due date. The primary outcome was the development of neonatal encephalopathy (defined as seizures, encephalopathy or brain injury caused by asphyxia or with unspecified cause). Covariates were selected as presumed confounders a priori. Results: 28.4% infants were born 1 or more weeks after their due date. An infant's risk of being born with encephalopathy was higher in the post 41 weeks group in the unadjusted (OR 1.40 (95% CI 1.32 to 1.49)) and final model (OR 1.38 (95% CI 1.29 to 1.47)), with the relative odds of encephalopathy increasing by an estimated 20% per week after the due date, and modified by maternal age (P=0.022). Conclusions: Singleton infants born at, or after, 41 weeks gestation have lower Apgar scores and higher risk of developing encephalopathy in the newborn period, and the association appeared more marked in older mothers. These data could be useful if provided to women as part of their decision-making.